POSITIVE EFFECTS OF BINAURAL MUSIC ON THE BRAIN - Sumerjana, Ketut; Sudirga, I Komang; Suteja, I Kt.; Suharta, I Wayan (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
Binaural music, which is characterized by the presentation of two slightly different sound frequencies to each ear, has gained increasing attention owing to its potential positive effects on the brain. Research suggests that binaural beats can influence cognitive and emotional states by modulating brainwave activity. When the brain perceives the difference between the two frequencies, it generates a third